2020
DOI: 10.2147/dmso.s265944
|View full text |Cite
|
Sign up to set email alerts
|

<p>Lycopene Improves the Metformin Effects on Glycemic Control and Decreases Biomarkers of Glycoxidative Stress in Diabetic Rats</p>

Abstract: Introduction Oxidative stress and exacerbated generation of advanced glycation end products (AGEs) participate in the onset of diabetic complications. Lycopene is a potent antioxidant; evidence accounts for its ability to mitigate diabetic disturbances, including the deleterious events of advanced glycation. Therefore, this carotenoid has emerged as a candidate to be used in combination with antidiabetic drugs, such as metformin, attempting to counteract the glycoxidative stress. This study invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 58 publications
2
27
0
Order By: Relevance
“…We demonstrated that lycopene treatment decreases the expressions of AGEs and RAGE as well as inhibits NF-кBp65 activation in the femurs and tibias of obese mice. These results were in line with the findings that lycopene is able to decrease the levels of plasma AGEs and renal RAGE [ 52 ] and suppress NF-кB activation in hyperglycemia rats and HK-2 cells [ 49 , 52 , 53 ]. In addition, lycopene was reported to inhibit ROS-induced NF-кB activation in pancreatic cancer cells [ 54 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We demonstrated that lycopene treatment decreases the expressions of AGEs and RAGE as well as inhibits NF-кBp65 activation in the femurs and tibias of obese mice. These results were in line with the findings that lycopene is able to decrease the levels of plasma AGEs and renal RAGE [ 52 ] and suppress NF-кB activation in hyperglycemia rats and HK-2 cells [ 49 , 52 , 53 ]. In addition, lycopene was reported to inhibit ROS-induced NF-кB activation in pancreatic cancer cells [ 54 ].…”
Section: Discussionsupporting
confidence: 89%
“…The sustained high levels of ROS may be associated with heightened AGE expressions upon hyperglycemia stimulation [ 49 ], which further induces NF-кB activation and subsequent bone resorption [ 50 , 51 ]. We demonstrated that lycopene treatment decreases the expressions of AGEs and RAGE as well as inhibits NF-кBp65 activation in the femurs and tibias of obese mice.…”
Section: Discussionmentioning
confidence: 99%
“…Figueriredo et al [ 275 ] reported that a combination of lycopene with metformin had an additive effect on improvements in postprandial blood glucose levels, dyslipidaemia, and antioxidant status. The investigation was performed in rats, and STZ-induced diabetic rats were treated with lycopene (45 mg/kg) and metformin (250 mg/kg) alone and in combination for 35 days.…”
Section: Health Effectsmentioning
confidence: 99%
“…Although insulin and anti-diabetic drugs are usually effective, most therapies fail to control long-term hyperglycemia. 6 This can actually be overcome by increasing the dose of the drug, but the risk of side effects will also increase, especially in patients with impaired kidney function, it may cause problems. [6][7][8] In addition, it can also be treated with combination therapy, either with conventional anti-diabetic drugs from different groups or with natural bioactive compounds.…”
Section: Introductionmentioning
confidence: 99%
“…6 This can actually be overcome by increasing the dose of the drug, but the risk of side effects will also increase, especially in patients with impaired kidney function, it may cause problems. [6][7][8] In addition, it can also be treated with combination therapy, either with conventional anti-diabetic drugs from different groups or with natural bioactive compounds. [9][10][11] One of the natural bioactive compounds that has received much attention because it has great potential in the treatment and prevention of chronic diseases is lycopene.…”
Section: Introductionmentioning
confidence: 99%